Disease of cowpea (Vigna unguiculata (L.) Walp) in Nigeria - Williams, R.J. (Informa UK Limited, 1975)
The known viral, fungal and bacterial diseases of cowpea in Nigeria are described with information on their importance and control. The complex of diseases undoubtedly represents a major constraint to more intensive and increased cowpea production. Although chemical control methods are available for some of the diseases, with the exception of seed dressing treatments they are probably not technically nor economically feasible at the peasant farmer level. Resistance to several of the major diseases has been identified which, if properly utilized, will remove many of the disease constraints to more intensive cowpea production in Nigeria. However, until both insect pests and diseases can be economically controlled, the cultivation of cowpea as a monocrop will not be feasible particularly in the forest region.